Shareholder monitoring and discretionary disclosure - Nagar, Venky; Schoenfeld, Jordan (Journal of Accounting and Economics, 2021)
Theories of delegated monitoring predict that when public disclosure is costly, monitoring by a large investor leads management to supply more private information to that investor, and less public disclosure to other similarly aligned investors who free-ride off the monitor. We test this prediction in the setting where large shareholders contractually bind management to share private information. We find that after the execution of such contracts, firms improve their performance and reduce their public disclosures. Overall, our evidence supports the disclosure prediction of delegated monitoring theories, and is inconsistent with poor-performance and expropriation theories of disclosure.